Martienssen, Rex Distin. Repertory theatre working drawing. 1928 final year student design project. Plan of tea room and dress circle. - Martienssen, Rex Distin (My University, 2011)
Martienssen, Rex Distin. Repertory theatre. 1928 Final year student design project. Plan of tea room and dress circle.
Ink on canvas.
Keywords: Martienssen, Rex Distin. Repertory theatre. Plan tea room and dress circle.